Proceeding Book: The 3rd International Conference On Health Science 2016 "Optimizing the Mental Health under SDGs" November 6st 2017, Hotel Inna Garuda - Prosiding (Poltekes Yogyakarta, 2016)
Proceeding Book: The 3rd International Conference On Health Science 2016 "Optimizing the Mental Health under SDGs" November 6st 2017, Hotel Inna Garuda